2016
DOI: 10.1177/0394632016638668
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress in the pathophysiology of Toxoplasma gondii infection

Abstract: Oxidative stress (OS) plays an essential role in the pathogenesis of common neurodegenerative diseases. We have previously shown that Toxoplasma gondii (T. gondii) induces high nitric oxide (NO) production, glial activation, and apoptosis that altogether cause severe neuropathology in toxoplasma encephalitis (TE). The objective of this study was to investigate the cytotoxic effect of OS and to identify a correlation between the causes of T. gondii induced neuropathology. Expression levels of glutathione reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 59 publications
5
34
0
Order By: Relevance
“…Toxoplasma -mediated oxidative stress (OS) is suggested to take part in the mechanism of neuropathology and neurodegeneration. [ 22 ] A pro-inflammatory immune reaction, dominated by Th1 and Th17 cytokines, particularly interferon (IFN-γ) and TNF-α, is triggered by Toxoplasma infection. [ 23 ] IFN-γ is the main and crucial cytokine for defense against T. gondii , particularly in central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…Toxoplasma -mediated oxidative stress (OS) is suggested to take part in the mechanism of neuropathology and neurodegeneration. [ 22 ] A pro-inflammatory immune reaction, dominated by Th1 and Th17 cytokines, particularly interferon (IFN-γ) and TNF-α, is triggered by Toxoplasma infection. [ 23 ] IFN-γ is the main and crucial cytokine for defense against T. gondii , particularly in central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…It often induces chain reactions in the biological and chemical processes, and inflammation, lack of energy by the cells, excitotoxicity, apoptosis, and oxidant stress may be caused as a result [6]. Among the previously mentioned processes, oxidative stress plays a pivotal role [7]. The promotion of inflammation and other reactions leads to the exacerbation of oxidative stress because oxidation aggravates inflammation and other reactions, which is a vicious cycle [8].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study illustrated that MDA serum level was high in patients with acute toxoplasmosis compared with controls due to induction of oxidative stress and lipid peroxidation. Dincel and Atmaca's study (19) confirmed that high level of MDA is associated with acute toxoplasmosis due to induction of oxidative stress and reduction of endogenous anti-oxidant capacity.…”
Section: Discussionmentioning
confidence: 84%